Host Preference Vegetables of Tobacco Whitefly Bemisia tabaci (Gennadius, 1889) in Nepal - Sharma, Mohan; Budha, Prem Bahadur (Journal of Institute of Science and Technology, 2015)
The host preference of whitefly Bemisia tabaci was experimented in four economically important vegetable plants viz. tomato, brinjal, capsicum and cucumber in 2012-2013. It was found that preference of whitefly for feeding under both conditions free-choice and no-choice was significantly different after 24 hours, 48 hours, 72 hours and 96 hours. Cucumber was the most preferred host plant for oviposition while capsicum was the least. Journal of Institute of Science and Technology, 2015, 20(1): 133-137